Operando monitoring of ion activities in aqueous batteries with plasmonic fiber-optic sensors - Wang, Runlin; Zhang, Haozhe; Liu, Qiyu; Liu, Fu; Han, Xile; Liu, Xiaoqing; Li, Kaiwei; Xiao, Gaozhi; Albert, Jacques; Lu, Xihong; Guo, Tuan (Nature communications, 2022)
Understanding ion transport kinetics and electrolyte-electrode interactions at electrode surfaces of batteries in operation is essential to determine their performance and state of health. However, it remains a challenging task to capture in real time the details of surface-localized and rapid ion transport at the microscale. To address this, a promising approach based on an optical fiber plasmonic sensor capable of being inserted near the electrode surface of a working battery to monitor its electrochemical kinetics without disturbing its operation is demonstrated using aqueous Zn-ion batteries as an example. The miniature and chemically inert sensor detects perturbations of surface plasmon waves propagating on its surface to rapidly screen localized electrochemical events on a sub-μm-scale thickness adjacent to the electrode interface. A stable and reproducible correlation between the real-time ion insertions over charge-discharge cycles and the optical plasmon response has been observed and quantified. This new operando measurement tool will provide crucial additional capabilities to battery monitoring methods and help guide the design of better batteries with improved electro-chemistries.